Mawlid as a Musical Form in Turkish Religious Music - Eren Köksal (İslami İlimler Dergisi)
The term Mawlid in Islamic culture, stands for many concepts from literature to fine arts, sociological phenomena to religious services and musical practises. Literally meaning the birth place and time, mawlid especially refers to the Holy Birth of the Prophet Muhammad (Blessings of Allah be upon Him and His household - pbuh), the commemoration ceremonies held on the occasion of the birth anniversary and the literary texts written for the observance of this very special day. In this respect many mawlid verses were written and Vesîletü’n-necât (Wasilat al-Najat) by Süleyman Chelebi has gained great reputation in Ottoman society. Therefore, the recitation of this certain mawlid verse has become a tradition and turned self later into a musical form with compositions and improvisational recitations. So, the musical recitation of Mawlid verse has turned into an official musical ceremony in time and settled in Turkish music tradition as a religious musical form. This study regards mawlid as a musical form and examines its performers, performance methods, musical characteristics. In addition to this, it also defines other religious music forms taking place in the mawlid ceremonies.